2019
DOI: 10.1136/bmj.l6322
|View full text |Cite
|
Sign up to set email alerts
|

Political events and mood among young physicians: a prospective cohort study

Abstract: ObjectiveTo study the effects of recent political events on mood among young physicians.DesignProspective cohort study.SettingUnited States medical centres.Participants2345 medical interns provided longitudinal mood data as part of the Intern Health Study between 2016 and 2018.Main outcome measuresMean mood score during the week following influential political and non-political events as compared with mean mood during the preceding four week control period.ResultsWe identified nine political events and eight n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…We omit the initial incident week in these estimates because number of incidents per week and national interest were not simultaneously modeled, but Model 2c estimates suggest 0.26 additional poor mental health days in the incident week. The temporary nature of population-level effects is consistent with prior research on societal stressors (e.g., terrorist acts, controversial political events), although the identified harmful effects on mental health have spanned periods of weeks to a few months (4,18,31). Integrating measures of the timing of public interest or distress may advance this research on the duration and scale of spillover effects from societal stressors.…”
Section: Discussionsupporting
confidence: 72%
“…We omit the initial incident week in these estimates because number of incidents per week and national interest were not simultaneously modeled, but Model 2c estimates suggest 0.26 additional poor mental health days in the incident week. The temporary nature of population-level effects is consistent with prior research on societal stressors (e.g., terrorist acts, controversial political events), although the identified harmful effects on mental health have spanned periods of weeks to a few months (4,18,31). Integrating measures of the timing of public interest or distress may advance this research on the duration and scale of spillover effects from societal stressors.…”
Section: Discussionsupporting
confidence: 72%
“…Of those studies, there are only a handful to date that used daily diary or ecological momentary assessment (EMA) methods (e.g., via smartphones) to assess the impact of stressors on students' daily lives. The few existing studies have focused primarily on U.S. presidential elections and other U.S. events (e.g., the Las Vegas shooting; Frank et al, 2019;Roche & Jacobson, 2019). The idea of tracking participants in daily life is many decades old and was formally introduced by Larson and Csikszentmihalyi (1983) as "a research procedure that consists of asking individuals to provide systematic self-reports at random occasions during the waking hours of a normal week [to obtain] reports about people's experiences as they occur" (p. 41).…”
mentioning
confidence: 99%
“…Previous research on migration of health workers has showed that in addition to both objective practical considerations, such as availability of public services like schools, cost of living, as well as work place factors such as staffing levels, teaching and professional support, language and ties to host and origin nation are important factors determining migration [ 15 16 ]. Moreover, a recent study highlighted the relationship between Brexit and adverse effects on mood of young doctors connected to political events [ 17 ], which demonstrates the importance of socio-political factors acting as push factors in migration decisions.…”
Section: Introductionmentioning
confidence: 99%